Budget Interconnection of The Aceh Special Autonomy Fund in An Islamic Perspective - Ramzani P, Ikbal (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Objective study This For know How policy preparation budget And its use , as well as For know application of the drafting model And usage budget fund autonomy special ones reviewed from perspective maqashid sharia . Method study This use method qualitative descriptive , ie something analysis that collects , organizes , manages , and analyze data , so that later can give description about something circumstances certain so that can withdrawn conclusion . Application​ preparation And use budget fund autonomy special the more on dimensions field infrastructure , empowerment economy people , alleviation poverty , education , health , social And Aceh’s specialty . Results study This show that application preparation And use fund autonomy special Not yet fully dominate dimensions dharuriyyah consisting of from religious protection ( hifẓ al- dīn ), protection soul ( hifẓ al- nafs ), protection reason ( hifẓ al-’ aql ), protection offspring ( hifẓ al- nasl ), protection treasure ( hifẓ al-mal ), and protection environment life ( hifẓ al- biah ). So that budget area can be confirmed For furthermore can projected For increase well-being public Aceh with base values Islam.